Operationalizing Postdischarge Recovery From Laparoscopic Sacrocolpopexy for the Preoperative Consultative Visit. Issue 10 (October 2021) - Heit, Michael; Carpenter, Janet S.; Chen, Chen X.; Rand, Kevin L.
Abstract : (Abstracted from Female Pelvic Med Reconstr Surg 2021;27:427–431) One of the most common questions from patients following surgery is: "What is my expected recovery time?" The answer serves as a benchmark to assess their progress against those undergoing similar procedures. Not addressing this expectation can result in poor patient satisfaction.